2014
DOI: 10.1093/ntr/ntu135
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Smokers’ Perceived Importance of the Appearance of Cigarettes/Cigarette Packs and Smoking Sensory Experience: A Structural Equation Model

Abstract: These findings support the regulation of the appearance of cigarettes/cigarette packs to reduce cigarettes' appeal and abuse liability in line with Article 11 of WHO's Framework Convention on Tobacco Control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Similar to packaging research, having warnings constantly ‘at hand’ will either continually, or at least periodically, remind smokers on the dangers associated with tobacco use and prompt quitting intentions . This allows cigarette stick warnings the potential to be as effective or more effective than current packaging warnings in reducing tobacco use . However, similar to graphic images on cigarette packaging, cigarette stick warnings would need to evoke a significant emotional response and ensure accurate perceptions of risk and increased quit intentions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to packaging research, having warnings constantly ‘at hand’ will either continually, or at least periodically, remind smokers on the dangers associated with tobacco use and prompt quitting intentions . This allows cigarette stick warnings the potential to be as effective or more effective than current packaging warnings in reducing tobacco use . However, similar to graphic images on cigarette packaging, cigarette stick warnings would need to evoke a significant emotional response and ensure accurate perceptions of risk and increased quit intentions .…”
Section: Discussionmentioning
confidence: 99%
“…[29] This allows cigarette stick warnings the potential to be as effective or more effective than current packaging warnings in reducing tobacco use. [14,17,37] However, similar to graphic images on cigarette packaging, cigarette stick warnings would need to evoke a significant emotional response and ensure accurate perceptions of risk and increased quit intentions. [38] Many pharmacists in the survey and interviews cited the health warnings on cigarette sticks as being 'in your face' and likely to attract the attention of the smoker and onlookers.…”
Section: Discussionmentioning
confidence: 99%
“…32 For example, one recent study identified a series of mediational pathways through which health warnings lead to quit attempts, 12 while another used structural equation models to explore associations between aspects of cigarette and cigarette packaging appeal, and cigarette consumption and quit attempts. 33 In addition, longitudinal studies have established that quitting-related cognitions and microindicators of concern predict attempts to quit. 17 34–37 Studies that more thoroughly investigate the pathways through which PP and GHW policies lead to changes in smoking behaviours are critical.…”
Section: Discussionmentioning
confidence: 99%
“…Companies have an incentive to focus greater attention on packaging and the cigarette itself to convey brand image. 2 3 Ayo-Yusuf and Agaku 4 describe the cigarette itself as the ‘primary’ level of packaging, and argue that enhancements in cigarette packaging are associated with increased sales and also influence sensory perceptions around cigarettes in ways that are key to smoking behaviour and addiction.…”
Section: Introductionmentioning
confidence: 99%